Collaborative Partnerships, Religious Reputation Culture, and Digital Tourism Promotion in Support of Halal Tourism Villages - Windi Novia Ratri Wardhani; Purnomo Purnomo; Ratih Pratiwi (IQTISHADIA, 2023)
This study focuses on two primary aspects of investigation. Firstly, it examines the digital methods that Small to Medium Tourism Enterprises (SMTEs) utilize and collaborative patterns with branding strategies to cultivate halal tourism villages. It employs a qualitative descriptive approach within the social phenomenology framework. Secondly, it identifies the most suitable alternative for SMTEs’ development using a Quantitative Strategic Planning Matrix (QSPM). The research concludes that enhancing SMTEs involves a multifaceted approach, including effective planning, digital transformation, fostering collaboration, and investing in halal-friendly infrastructure with standardization in halal certification. Through a qualitative approach and QSPM analysis, the study identifies strategic priorities like collaborative partnerships, religious reputation culture implementation, and digital tourism promotion as crucial strategies for SMTEs’ success. This research significantly contributes to the development of halal tourism enterprises by involving a unique context, employing less common methodology, and focusing on sustainable development. The limitations of this study pertain to the impact of uncontrollable external changes, while the future research agenda explores predictive modeling and regional comparisons to advance further the understanding of strategy outcomes in halal tourism development.